Zachowania higieniczne dzieci w wieku przedszkolnym w ocenie rodziców = Hygiene behavior among preschool children in the opinion of their parents - Skonieczna, Joanna; Jankowska, Martyna; Olejniczak, Dominik; Boratyński, Wojciech (Journal of Education, Health and Sport, 2015)
Skonieczna Joanna, Jankowska Martyna, Olejniczak Dominik, Boratyński Wojciech. Zachowania higieniczne dzieci w wieku przedszkolnym w ocenie rodziców = Hygiene behavior among preschool children in the opinion of their parents. Journal of Education, Health and Sport. 2015;5(9):109-116. ISSN 2391-8306. DOI10.5281/zenodo.30044 http://dx.doi.org/10.5281/zenodo.30044 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A109-116 https://pbn.nauka.gov.pl/works/616441 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.07.2015. Revised 24.08.2015. Accepted: 24.08.2015. Zachowania higieniczne dzieci w wieku przedszkolnym w ocenie rodziców Hygiene behavior among preschool children in the opinion of their parents Skonieczna Joanna, Jankowska Martyna, Olejniczak Dominik, Boratyński Wojciech Zakład Zdrowia Publicznego, Warszawski Uniwersytet Medyczny Public Health Department, Medical University of Warsaw Słowa kluczowe: higiena, higiena jamy ustnej, promocja zdrowia, przedszkolaki. Key words: health promotion, hygiene, oral hygiene, preschool. Streszczenie Wprowadzenie: Według wielu autorów przedszkole powinno być pierwszym etapem edukacji dla wszystkich dzieci. Dzieci należy wychowywać i kształcić dzieci w obszarze czynności samoobsługowych, nawyków higienicznych i kulturowych a także wychowania zdrowotnego i kształtowania sprawności fizycznej. Cel pracy: ocena wpływu rodziców/opiekunów prawnych i przedszkola w kontekście formowania nawyków higienicznych u dzieci w wieku przedszkolnym. Materiał i metoda: Badanie zostało przeprowadzone metodą sondażu diagnostycznego. Wykorzystanym narzędziem był autorski kwestionariusz. Grupę badaną stanowiło 134 rodziców/opiekunów prawnych dzieci w wieku 3 – 6 lat. Wśród odpowiadających rodziców/opiekunów prawnych większość stanowiły kobiety (90% respondentów) Wyniki: Zdecydowana większość (86%) rodziców uważa, że ich dzieci potrafią samodzielnie myć i płukać zęby. Blisko 52% małoletnich częściej niż raz dziennie szczotkuje zęby. Ponad połowa badanych (54%) odpowiedziała, iż dziecko regularnie odbywa wizyty u dentysty. Rodzice w większości (75%) deklarują uczestnictwo ich dziecka w dodatkowych zajęciach ruchowych. Wnioski: Przedszkole wspólnie z rodzicami powinno edukować dziecko w zakresie zachowań higienicznych. Gabinety stomatologiczne powinny być odpowiednio przystosowane do potrzeb najmłodszych dzieci w celu zminimalizowania strachu przed dentystą. Rodzice w zbyt niskim stopniu zainteresowani są działaniami na rzecz promocji zdrowia realizowanymi w przedszkolu. Należy zintensyfikować działania mające na celu edukację rodziców w tym zakresie. Abstract Introduction: Preschool should be the first step in education for all children. Children should be educated in self-service activities, hygiene and cultural habits as well as health education and physical fitness. Aim: The evaluation of parents and preschool influence on the hygienic habits in children of preschool age. Material and Methods: The study was conducted using a diagnostic survey and a questionnaire designed by the author.. The study included 134 parents / legal guardians of children ages 3 - 6 years, most women (90%). Results: The vast majority (86%) of parents believe that their children can brush their teeth alone. Nearly 52% of children brushing teeth more than once a day. More than half of respondents (54%) answered that the child takes the dentist regularly. Parents (75%) declare their child's participation in additional physical activities. Conclusions: Kindergarten together with their parents should educate children about hygiene behavior. Dental services should be properly adapted to the needs of the youngest children in order to minimize the fear of the dentist. Parents are not interested in the activities on health promotion implemented in kindergarten. Education of parents in this area should be intensified.